Understanding instructors’ tablet adoption for note-taking in interpreting: insights from the GETAMEL model - Tian, Yuan; Wang, Yuying (Frontiers in Education, 2024)
With the rise in popularity of tablets, professional interpreters were among the early adopters who integrated them into their workflow. Tablets have also become an indispensable tool for students, including those studying interpreting, who utilize them in the classroom for various purposes, such as note-taking. However, despite this growing trend, the traditional practice of pen-and-paper note-taking remains prevalent. Additionally, current interpreting textbooks primarily focus on teaching pen-and-paper note-taking skills. As interpreting instructors, it is crucial for us to familiarize ourselves with the use of tablets for note-taking in consecutive interpreting (CI). This will enable us to adapt our teaching methods accordingly and cater to the needs of the “iPad Kids” generation. The purpose of this study is to use quantitative method to examine the factors that contribute to the adoption of tablets for note-taking by instructors in the classroom environment. A questionnaire was developed based on the General Extended Technology Acceptance Model for E-learning (GETAMEL) framework. The questionnaire was distributed to teachers at prominent foreign language universities, foreign language faculties in select comprehensive universities and translation training institutions across Chinese Mainland and Macao Special Administrative Region of China. To provide comprehensive insights into the variables under study, descriptive statistics were generated using both SPSS 25.0 and Excel. These tools facilitated the production of detailed data summaries, offering valuable insights into the research variables. The obtained results provide insights into various aspects, including instructors’ knowledge levels and usage of tablet interpreting in university classrooms, their attitudes toward integrating tablet interpreting into teaching, and the key factors that influence their decisions to adopt tablet interpreting in their classroom practices. The findings suggest the existence of additional external factors that could be incorporated into the existing model. The paper concludes with recommendations on how to promote the integration of technology into teaching practices for interpreting instructors.